Determinación del impacto de la lluvia ácida en tres sectores (norte, centro y sur) de la ciudad de Latacunga período 2015 - Aimacaña Toapanta, Fernanda Maribel (2016)
This research was determined the presence of acid rain in Latacunga city, it started with a depth analysis of influent factors such as: the industrial sector, the vehicular flow, the wind addressing and population density, they permitted to establish the main three referential points in order to show and collect the raindrops dividing the city into three sections: north, downtown and south. The monitor was done during December 2015 and January 2016, developing two samples for each one were developed for each case, with a total of six samples, they were collected within few hours of precipitation; it was followed by the protocol of sampling established by the NTE INEN 2 169: 98 and then they were delivered for its analysis to the LANCAS - INAMHI analytical laboratory where they were analyzed on based to the established methods by the laboratory parameters about pH, conductivity, nitrates and sulfates….